The spy who came in from the cold - Cornwell, David John Moore 1931- (New York Coward-McCann, 1964)
A veteran spy wants to "come in from the cold" to retirement. He undertakes one last assignment in which he pretends defection and provides the enemy with sufficient evidence to label their leader a double agent.
A novel.